Role of exosomal noncoding RNA in esophageal carcinoma - Si, Mao-Yan; Rao, Ding-Yu; Xia, Yao; Sang, Cheng-Peng; Mao, Kai-Yun; Liu, Xiang-Jin; Zhang, Zu-Xiong; Tang, Zhi-Xian (Frontiers in Oncology, 2023)
Esophageal cancer is a common malignant tumor with a high degree of malignancy. Understanding its pathogenesis and identifying early diagnostic biomarkers can significantly improve the prognosis of esophageal cancer patients. Exosomes are small double-membrane vesicles found in various body fluids containing various components (DNA, RNA, and proteins) that mediate intercellular signal communication. Non-coding RNAs are a class of gene transcription products that encode polypeptide functions and are widely detected in exosomes. There is growing evidence that exosomal non-coding RNAs are involved in cancer growth, metastasis and angiogenesis, and can also be used as diagnostic and prognostic markers. This article reviews the recent progress in exosomal non-coding RNAs in esophageal cancer, including research progress, diagnostic value, proliferation, migration, invasion, and drug resistance, provide new ideas for the precise treatment of esophageal cancer.